Ethyronine-based perovskite battery and preparation method thereof
By using ethionine as the interface modification layer on the buried interface of perovskite photovoltaic devices, the interface defects and material solubility problems of perovskite photovoltaic devices are solved, and efficient photovoltaic performance improvement and stability enhancement are achieved.
Patent Information
- Application Number
- CN202510369224.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The density of the buried interface defect state of perovskite photovoltaic devices has a high density, resulting in a degradation of photovoltaic performance. In addition, the functional interface materials have a high solubility in the perovskite precursor solvent, which is easy to be washed away during spin coating and cannot achieve its maximum potential.
Ethionine (DLEO) is used as the interface modification layer, and an interface modification layer of 5~10nm is formed on the SnO2 surface by spin coating and annealing to regulate the crystallization kinetics and interface energy level matching of the perovskite film.
Effectively passivate the oxygen vacancies defects on the surface of SnO2, form a high-quality and high-stability perovskite film, improve the performance and stability of photovoltaic devices, and significantly improve the photoelectric conversion efficiency and long-term stability.
Smart Images

Figure CN119894219A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor technology and relates to a novel interface-modified perovskite photovoltaic device, and specifically relates to an ethionine-based perovskite battery and a preparation method thereof. Background Art
[0002] Due to the unique optoelectronic properties of perovskite materials, perovskite solar cells prepared based on them have developed rapidly, and the photoelectric conversion efficiency of perovskite devices has reached 27%. The top-down crystallization process of perovskite will cause the defect state density at the buried interface of perovskite to be much higher than that of the top surface of perovskite. These defect states will capture photogenerated carriers and cause non-radiative recombination losses, thereby reducing the photovoltaic performance of perovskite. In addition, these defects will also become the main invasion sites for external factors such as water and oxygen to corrode perovskite, seriously affecting the long-term stability of perovskite devices. The problems of large-area preparation uniformity and long-term working stability have seriously hindered the commercial development of perovskite photovoltaic technology.
[0003] Related researchers have found that introducing an interface layer with molecular bridging effect at the buried interface of perovskite can effectively solve the buried interface problem of perovskite solar cells. However, most of the functional organic small molecules currently used show good solubility in polar solvents commonly used to prepare perovskite precursors, such as N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). When the perovskite film is deposited sequentially on the deposited functional material, the underlying interface material may be washed away after spin coating the perovskite precursor solution, thereby preventing the interface material from achieving its maximum potential. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention proposes an ethionine-based perovskite cell and a preparation method thereof, using ethionine (DLEO) to construct a benign buried interface, improving the performance and stability of perovskite photovoltaic devices, and solving the problem that the existing functional materials have good solubility in the common solvents used in the perovskite precursors, resulting in a high probability of destroying the underlying functional materials when spin-coating the perovskite film, and failing to play a good passivation role.
[0005] An ethionine-based perovskite cell comprises, from bottom to top, a conductive glass, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal back electrode. An interface modification layer is provided between the electron transport layer and the perovskite light absorption layer, and the interface modification layer is ethionine with a thickness of 5 to 10 nm.
[0006] Preferably, the electron transport layer is SnO2 with a thickness of 20-30 nm.
[0007] Preferably, the component of the perovskite light absorbing layer is FA (1-x) MAx PbI3, where x is 0~0.1 and the thickness is 600~800nm.
[0008] A method for preparing a perovskite battery based on ethionine, the specific steps are as follows:
[0009] Step 1: ultrasonically clean the etched conductive glass using deionized water, acetone and ethanol in sequence, and then dry it for later use.
[0010] Step 2: Plasma-treating the conductive glass obtained in step 1, and then spin-coating a layer of SnO2 film on the surface thereof.
[0011] Preferably, the SnO2 dispersion is diluted with deionized water, and the volume ratio of deionized water to the SnO2 dispersion is 3: 1. Then, the SnO2 film is spin-coated on the surface of the plasma-treated conductive glass to form a SnO2 film with a thickness of 20-30 nm.
[0012] Step 3: Use deionized water as a solvent to prepare an aqueous solution of 0.5-2.0 mg / mL of ethionine (DLEO). Deposit the DLEO aqueous solution on the surface of the SnO2 film by spin coating, and then perform annealing to form an interface modification layer with a thickness of 5-10 nm on the SnO2 surface.
[0013] Preferably, the annealing temperature is 100° C. and the ambient humidity is 30%-40%.
[0014] Step 4: Prepare the perovskite film by a two-step method, deposit the lead iodide precursor solution and the ammonium salt solution onto the surface of the interface modification layer prepared in step 3, and obtain a uniformly grown perovskite film after annealing.
[0015] Preferably, the lead iodide precursor solution and the ammonium salt solution are deposited onto the surface of the interface modification layer by spin coating, blade coating or slit coating.
[0016] Preferably, the annealing temperature is 150° C. and the ambient humidity is 30%-40%.
[0017] Step 5: depositing a hole transport layer on the surface of the perovskite film obtained in step 4.
[0018] Preferably, spiro-OMeTAD is spin-coated on the surface of the perovskite film at a speed of 3000-5000 rpm / s to deposit a hole transport layer.
[0019] Step 6: Deposit a metal back electrode on the surface of the hole transport layer by thermal evaporation to obtain a DLEO-modified perovskite solar cell.
[0020] Preferably, the metal back electrode is one of Ag, Au and Cu.
[0021] The present invention has the following beneficial effects:
[0022] By using DLEO as an interface modification layer and regulating the SnO2 surface, the oxygen vacancy defects on the SnO2 surface can be effectively passivated. At the same time, due to the sulfur, amino and carboxyl groups on the DLEO molecules, an effective chemical bridge can be formed between SnO2 and perovskite, regulating the crystallization kinetics of the perovskite film and optimizing the energy level matching of the perovskite bottom interface. The synergistic effect of the two provides a method for achieving a simple and reproducible preparation of high-quality, high-stability perovskite films and enhancing the stability of their photovoltaic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the structure of ethionine-based perovskite battery;
[0024] Figure 2 JV curve of SnO2 film in Examples 1 and 2.
[0025] Figure 3 SCLC curve diagram of SnO2 film in Examples 1 and 2.
[0026] Figure 4 XPS graph of SnO2 thin film in Examples 1 and 2.
[0027] Figure 5 AFM images of SnO2 films in Examples 1 and 2.
[0028] Figure 6 Surface SEM images of the perovskite films in Examples 1 and 2.
[0029] Figure 7 2 is the XRD diagram of the perovskite battery in Examples 1 and 2.
[0030] Figure 8 This is a graph showing the trend of changes in the stability test of perovskite solar cells in Examples 1 and 2.
[0031] Fig. 9 This is the TAS diagram of the perovskite battery in Examples 1 and 2. DETAILED DESCRIPTION
[0032] In order to more clearly understand the purpose, technical solutions and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited thereto.
[0033] Example 1
[0034] This example prepares a conventional perovskite cell, which includes conductive glass, an electron transport layer, a perovskite light absorption layer, a hole transport layer, and a metal back electrode from bottom to top, for comparative experiments to illustrate the advantages of the ethionine-based perovskite cell. The specific steps are as follows:
[0035] Step 1: The etched ITO conductive glass was ultrasonically cleaned with deionized water, acetone and ethanol for 15 min in sequence, then placed in an oven for drying at 80 °C for standby use, and then subjected to plasma treatment for 30 min.
[0036] Step 2: The SnO2 dispersion was diluted in deionized water at a volume ratio of 1:3, and then spin-coated on the surface of the plasma-treated conductive glass at a speed of 3000 rpm / s for 30 s. The film was then annealed on a 150 °C heating table for 30 min to obtain a SnO2 film with a thickness of 20 nm.
[0037] Step 3: Weigh 691.5 mg of PbI2, use 1 mL of a mixed solution of DMF and DMSO with a volume ratio of 9:1 as solvent, and stir at room temperature for 6 hours to obtain a lead iodide precursor solution. Weigh 90 mg of FAI, 7 mg of MAI, and 9 mg of MACl, use 1 mL of isopropanol solution as solvent, and stir at room temperature for 2 hours to obtain an ammonium salt solution.
[0038] Step 4: Prepare the perovskite film by a two-step method: spin-coat the lead iodide precursor solution on the surface of the SnO2 film at a speed of 1500 rpm / s for 30 s; then spin-coat the ammonium salt solution at a speed of 1800 rpm / s for 30 s. Then anneal at 150 °C in air for 15 min to obtain the perovskite film. The FA of the perovskite film 0.92 MA 0.08 PbI3,
[0039] Step 5: Spin-coat spiro-OMeTAD on the surface of the perovskite film at a speed of 4000 rpm / s to deposit a hole transport layer. Deposit Ag as a metal back electrode on the surface of the hole transport layer by thermal evaporation to obtain a perovskite solar cell.
[0040] Example 2
[0041] This example prepares a Figure 1 The ethionine-based perovskite cell shown includes, from bottom to top, a conductive glass, an electron transport layer, an interface modification layer, a perovskite light absorption layer, a hole transport layer, and a metal back electrode. The specific steps are:
[0042] Step 1: The etched ITO conductive glass was ultrasonically cleaned with deionized water, acetone and ethanol for 15 min in sequence, then placed in an oven for drying at 80 °C for standby use, and then subjected to plasma treatment for 30 min.
[0043] Step 2: The SnO2 dispersion was diluted in deionized water at a volume ratio of 1:3, and then spin-coated on the surface of the plasma-treated conductive glass at a speed of 3000 rpm / s for 30 s. The film was then annealed on a 150 °C heating table for 30 min to obtain a SnO2 film with a thickness of 20 nm.
[0044] Step 3: Dissolve 1.0 mg of ethionine in 1 mL of deionized water to prepare a DLEO aqueous solution. Deposit the DLEO aqueous solution on the surface of the SnO2 film by spin coating, and then perform a secondary annealing treatment at 100 °C for 10 min to form an interface modification layer with a thickness of 5 nm on the SnO2 surface.
[0045] The SnO2 film prepared in step 2 of Example 1 and the SnO2 film processed in step 3 of this example were tested for JV curve and SCLC curve. The results are as follows: Figure 2 , Figure 3 As shown. Figure 2 It can be seen that the conductivity of the SnO2 film in Example 1 is 7.00 × 10 -4 S m -1 In Example 2, the conductivity of the SnO2 film after DLEO treatment is 9.95 × 10 -4 S m -1 , has been significantly improved. Figure 3 It can be seen that the defect state density of the SnO2 film in Example 1 is 9.67 × 10 -3 cm -3 After DLEO treatment, the defect state density inside the SnO2 film is reduced to 9.02 × 10 -3 cm -3 .
[0046] The SnO2 films before and after DLEO treatment in Examples 1 and 2 were further tested by X-ray photoelectron spectroscopy (XPS). Figure 4 As shown in Figure 2, the oxygen vacancy defects on the surface of the SnO2 film after DLEO treatment in Example 2 are significantly reduced, indicating that DLEO can effectively passivate the surface defects of SnO2, which is beneficial to carrier transport. The morphology of the SnO2 film before and after DLEO treatment in Examples 1 and 2 was characterized by atomic force microscopy (AFM). The results are shown in Figure 2. Figure 5As shown, it can be seen that the surface root mean square (RMS) roughness of the SnO2 film after DLEO treatment is reduced from 2.29 nm to 2.10 nm compared with the SnO2 film in Example 1, indicating that the surface of the SnO2 film is smoother after DLEO treatment, which is conducive to the crystal growth of sequentially deposited perovskite film.
[0047] Step 4: Weigh 691.5 mg of PbI2, use 1 mL of a mixed solution of DMF and DMSO with a volume ratio of 9:1 as solvent, and stir at room temperature for 6 hours to obtain a lead iodide precursor solution. Weigh 90 mg of FAI, 7 mg of MAI, and 9 mg of MACl, use 1 mL of isopropanol solution as solvent, and stir at room temperature for 2 hours to obtain an ammonium salt solution.
[0048] Step 5: Prepare the perovskite film by a two-step method: spin-coat the lead iodide precursor solution on the surface of the interface modification layer at a spin-coating speed of 1500 rpm / s for 30 s; then spin-coat the ammonium salt solution at a spin-coating speed of 1800 rpm / s for 30 s. Then anneal at 150 °C in air for 15 min to obtain the perovskite film. The FA of the perovskite film 0.92 MA 0.08 PbI3,
[0049] Step 6: Spin-coat spiro-OMeTAD on the surface of the perovskite film at a speed of 4000 rpm / s to deposit a hole transport layer. Deposit Ag as a metal back electrode on the surface of the hole transport layer by thermal evaporation to obtain a DLEO-modified perovskite solar cell.
[0050] The perovskite solar cells prepared in Examples 1 and 2 were tested by scanning electron microscope (SEM), and the results are as follows: Figure 6 As shown in Figure 2, the grain size of the perovskite film after DLEO modification in Example 2 is significantly increased, and the grain boundaries are reduced. Figure 7 As shown, the study found that the introduction of DLEO can reduce the characteristic peak of PbI2 (2θ=12.7°) and weaken the preferred orientation crystallinity of the (111) crystal plane, indicating that DLEO can regulate the crystallization of perovskite to obtain high-quality films.
[0051] In order to determine the effect of DLEO treatment on the efficiency of perovskite solar cells, the perovskite solar cells prepared in Examples 1 and 2 were tested by JV curves, and the optimal photovoltaic parameters are shown in Table 1:
[0052] Table 1
[0053] Group Open Circuit Voltage (Volts) Short circuit current density (mA / cm2) Fill Factor efficiency(%) Example 1 1.06 25.36 0.83 22.31 Example 2 1.13 25.59 0.83 24.00
[0054] It can be seen from the data in Table 1 that the photoelectric conversion efficiency of the perovskite device is significantly improved after DLEO treatment.
[0055] The stability of the perovskite solar cells prepared in Examples 1 and 2 was tested. -2 , AM 1.5 G) to perform maximum power point steady-state tracking, the results are as follows Figure 8 As shown, it can be seen that after 400 hours of maximum power point tracking, the efficiency of the perovskite solar cell without DLEO treatment in Example 1 has decayed to 84% of the initial efficiency, while the efficiency of the perovskite device treated with DLEO prepared in Example 2 still maintains the initial 98%, indicating that the construction of a benign buried interface can achieve a simultaneous improvement in the efficiency and stability of perovskite photovoltaic devices.
[0056] In order to clarify the reasons for the improvement of perovskite device efficiency and stability, ultraviolet photoelectron spectroscopy (UPS) tests were performed on the perovskite before and after DLEO treatment. The results are shown in Table 2:
[0057] Table 2
[0058]
[0059] From the data in Table 2, it can be seen that the Fermi level (E Fermi levels ) has a Fermi level difference of 0.14 eV with SnO2 surface. The Fermi level of the bottom surface of the untreated perovskite (E Fermi levels ) and the Fermi level difference between the SnO2 surface is 0.15 eV, indicating that the establishment of a benign buried interface makes the energy levels between SnO2 and perovskite more matched, provides a more efficient electron extraction channel, and minimizes thermal relaxation losses. Therefore, the perovskite device based on DLEO treatment obtains a higher fill factor (FF).
[0060] The perovskite solar cells prepared in Examples 1 and 2 were subjected to thermal conductivity Sap (TAS) tests, and the results are as follows: Fig. 9 As shown, the density of deep level defect states in the perovskite film after DLEO treatment in Example 2 is significantly reduced, reducing carrier capture sites and inhibiting non-radiative recombination losses. Since defects are also invasion sites for water and oxygen in the air, the perovskite film after DLEO treatment also has better stability.
[0061] Example 3
[0062] In this example, an ethionine-based perovskite battery is prepared. On the basis of Example 2, the thickness of the SnO2 film is adjusted to 30 nm, the concentration of the ethionine aqueous solution is adjusted to 0.5 mg / mL, and the thickness of the interface modification layer is adjusted to 3 nm.
[0063] Example 4
[0064] In this example, an ethionine-based perovskite battery was prepared. Based on Example 3, the concentration of the ethionine aqueous solution was adjusted to 2.0 mg / mL.
[0065] Example 5
[0066] In this embodiment, an ethionine-based perovskite battery is prepared. On the basis of Embodiment 4, the thickness of the SnO2 film is adjusted to 25 nm, and the thickness of the interface modification layer is adjusted to 8 nm.
Claims
1. An ethionine-based perovskite cell, comprising, from bottom to top, a conductive glass, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal back electrode, wherein an interface modification layer is provided between the electron transport layer and the perovskite light absorption layer, characterized in that: The interface modification layer is ethionine and has a thickness of 5 to 10 nm.
2. The ethionine-based perovskite battery according to claim 1, characterized in that: The electron transport layer is SnO2 with a thickness of 20-30 nm.
3. The ethionine-based perovskite battery according to claim 1, characterized in that: The component of the perovskite light absorbing layer is FA (1-x) MA x PbI3, where x is 0~0.1 and the thickness is 600~800nm.
4. A method for preparing an ethionine-based perovskite battery, wherein a SnO2 film, an interface modification layer, a perovskite film, a hole transport layer and a metal back electrode are sequentially prepared on the surface of a conductive glass, characterized in that: The interface modification layer is obtained by spin coating a 0.5-2.0 mg / mL ethionine aqueous solution on the surface of the SnO2 film and then performing annealing treatment.
5. A method for preparing an ethionine-based perovskite battery according to claim 4, characterized in that: The specific steps are as follows: Step 1, ultrasonically clean the etched conductive glass using deionized water, acetone and ethanol in sequence, and then dry it for later use; Step 2, plasma treating the conductive glass obtained in step 1, and then spin coating a layer of SnO2 film on the surface thereof; Step 3, spin coating an ethionine aqueous solution on the surface of the SnO2 film, and then performing an annealing treatment to form an interface modification layer with a thickness of 5 to 10 nm on the SnO2 surface; Step 4: preparing a perovskite film by a two-step method, depositing a lead iodide precursor solution and an ammonium salt solution onto the surface of the interface modification layer prepared in step 3, and obtaining a perovskite film after annealing; Step 5, depositing a hole transport layer on the surface of the perovskite film obtained in step 4; Step 6: depositing a metal back electrode on the surface of the hole transport layer by thermal evaporation to obtain an ethionine-based perovskite solar cell.
6. A method for preparing an ethionine-based perovskite battery according to claim 5, characterized in that: The SnO2 dispersion was diluted with deionized water, with the volume ratio of deionized water to SnO2 dispersion being 3:1; it was then spin-coated on the surface of the plasma-treated conductive glass to form a SnO2 film with a thickness of 20-30 nm.
7. A method for preparing an ethionine-based perovskite battery according to claim 5, characterized in that: In step 3, the annealing temperature is set to 100°C, in step 4, the annealing temperature is set to 150°C, and the ambient humidity is 30%~40%.
8. The method for preparing a perovskite battery based on ethionine according to claim 5, characterized in that: The lead iodide precursor solution and the ammonium salt solution are deposited on the surface of the interface modification layer by spin coating, scraping coating or slit coating.
9. A method for preparing an ethionine-based perovskite battery according to claim 5, characterized in that: The spiro-OMeTAD was spin-coated on the surface of the perovskite film at a speed of 3000-5000 rpm / s to deposit a hole transport layer.
10. The method for preparing a perovskite battery based on ethionine according to claim 5, characterized in that: The metal back electrode is one of Ag, Au and Cu.
Citation Information
Patent Citations
Preparation method of amino acid modified tin oxide sol
CN118204017A
Preparation method of interface modification layer, trans-perovskite cell and preparation method of trans-perovskite cell
CN118301960A
Synthesis of high density, vertically aligned titanium dioxide nanorod on transparent conducting glass substrate and its use in photo-electrode of dye-sensitized solar cells
KR1020130013372A
KR20240139810A